Exponential decay for a strain gradient porous thermoelasticity with second sound - Ahmima, Afaf; Fareh, Abdelfeteh (Armenian Journal of Mathematics, 2022)
In this paper, we consider a strain gradient porous elastic bar subjected to a thermal disturbance modelled by Cattaneo’s law for heat conduction. We use the semigroup approach to prove the existence of a unique weak solution. Although the thermal dissipation induced by the second sound thermoelasticity is weaker than that caused by the classical heat conduction, we prove that the solution decays exponentially.